The waterbearers : a memoir of mothers and daughters - Bonét, Sasha (Alfred A. Knopf, 2025)
"A sharp, tender, sweeping history of three single Black mothers-the author's grandmother, mother, and the author herself-interwoven with the stories of the Black women they saw on the screen and heard on the radio every day. Here is a masterpiece of life writing by a thrilling new voice, a writer who will remake how we think of generations. We begin in a house along a bayou in Texas, a home bought and paid for-and run-by the author's grandmother. Betty Jean spent twenty summers in the swamplands of Louisiana as a cotton tenant farmer before going north to Texas in the Great Migration. It was there that she would raise her eleven children, most by different fathers whom she rarely kept around. "If she tended the land and the laundry," Bonét writes, "what were the uses of a man?" Mama Connie, one of those eleven, grew up under her mother's controlling hand and struggled to forgive, vowing that her life would be different. But when it came to having children of her own, she was more like Betty Jean than she cared to admit. She made her home just a few blocks away, and received the same nickname as her mother, the "Black Widow." And, like her mother before her, Connie's sweat was the founding salt of her own universe. Today, Sasha Bonét, like each woman before her, wrangles with the pull of her mother's orbit, the austerity and love from which it came. She is the first in her family to look to the past in order to radically reimagine her future, and the future of her daughter. In fostering a community of motherhood, Bonét interrogates all aspects of being a mother-escape and promise, burden, assent, and rebellion-not just for those who came before her, but for those Black women with whom society is acquainted, too: Nina Simone; Oprah Winfrey; Audre Lorde, and Darnella Fraiser, who filmed the murder of George Floyd and mobilized the world"-- Provided by publisher.